Nitric Oxide, Epileptic Seizures, and Action of Antiepileptic Drugs - Banach, Monika; Piskorska, Barbara; J. Czuczwar, Stanislaw; K. Borowicz, Kinga (CNS & Neurological Disorders - Drug Targets, 2011)
Nitric oxide (NO) plays a variety of physiological and pathological roles in mammalian cells. In the central nervous system NO may behave as a second messenger, neuromodulator, and neurotransmitter, which may suggest an essential role of this gaseous molecule in epilepsy and epileptogenesis. The aim of this review is to survey the current literature in terms of experimental and clinical evidence of anti- or proconvulsive properties of NO and its implications in the anticonvulsive action of antiepileptic drugs. Up-to-date multiple NO synthase (NOS) inhibitors and donors of NO were used in a plethora of seizure models (e.g. electrically and pharmacologically-evoked convulsions, amygdala-kindled seizures). Reported results vary depending on the seizure model, kind and doses of pharmacological tools used in experiments, and route of drug administration. The most thoroughly tested NOS inhibitor was 7- nitroindazole (7-NI), which presented anticonvulsive properties in most known models of seizures. The clear-cut proconvulsant action of 7-NI was observed only in kainate-, nicotine-, and soman-induced convulsions in rodents. This NOS inhibitor enhanced the anticonvulsant action of almost all available classic and second-generation antiepileptic drugs except tiagabine, felbamate, and topiramate. The effect of NG-nitro-L-arginine methyl ester was not so unambiguous. In pentylenetetrazole, pictotoxin, and N-methyl-Daspartate seizure models the inhibitor exhibited dose-dependent bidirectional action. NG-nitro-L-arginine methyl ester potentiated the efficacy of diazepam and clonazepam, diminished that of valproate and phenobarbital, but did not affect the anticonvulsant action of phenytoin and ethosuximide. On the other hand, NG-nitro-L-arginine, was anticonvulsant in nicotine-, glutamate-, and hyperbaric O2- evoked seizures, and proconvulsant in pilocarpine-, kainate-, bicuculline-, aminophylline-, and 4-aminopyridine-induced convulsions. NG-nitro-L-arginine remained without effect on the anticonvulsant action of both classic (valproate, phenobarbital, diazepam) and new generation (oxcarbazepine, felbamate, and ethosuximide) antiepileptic drugs. The action of ethosuximide was even impaired. Summing up, in the present state of knowledge the only reasonable conclusion is that NO behaves as a neuromodulator with dual - proconvulsive or anticonvulsive - action.
Keywords: Seizures